Design, Physicochemical, Pharmacokinetic, Drug Likeness, and In-Silico Prediction of Toxicity, Adverse Effects and Biological Activity of Fulvic Acid and Humic Acid as Potent Anti-Diabetic Agents - Rastogi, Rohan; Rastogi, Harshit; Bhaskar, Aryan; Bhardwaj, Abhay; Pathak, Anuj; Raghavendra Rao, N.G.; Sharma, Deepak (Journal of Neonatal Surgery, 2025)
This study explores the potential of fulvic acid and humic acid derivatives as anti-diabetic agents through computational methods. Diabetes, a chronic metabolic disorder characterized by high blood sugar levels, affects millions globally. This research investigates the use of derivatives of fulvic acid and humic acid, compounds found in Shilajit, as potential treatments by overcoming the insulin resistance developed in the body in Type-2 Diabetes. The study involves in-silico docking simulations to evaluate the interaction of these derivatives with the Extracellular Signal-regulated Kinase 2 (ERK2) receptor, a key target in diabetes therapy. The analysis includes predicting physicochemical properties, pharmacokinetics, drug-likeness, toxicity, and adverse effects of the derivatives. Results indicate that several fulvic acid and humic acid derivatives exhibit strong binding affinities to the ERK2 receptor. The computational analysis suggests that these derivatives possess favourable pharmacokinetic properties, indicating good oral bioavailability and absorption. Furthermore, toxicity predictions suggest that these compounds may have a relatively low risk of adverse effects. In conclusion, this in-silico study identifies promising fulvic acid and humic acid derivatives as potential anti-diabetic agents. The findings support further research and development of these compounds for diabetes treatment.